(untitled) (Clinics, 2012)
OBJECTIVE: Genomic instability is a hallmark of malignant tissues. In this work, we aimed to characterize nuclear and mitochondrial instabilities by determining short tandem repeats and somatic mitochondrial mutations, respectively, in a cohort of Brazilian sporadic breast cancer cases. Furthermore, we performed an association analysis of the molecular findings and the clinical pathological data. METHODS: We analyzed 64 matched pairs of breast cancer and adjacent non-cancerous breast samples by genotyping 13 nuclear short tandem repeat loci (namely, D2S123, TPOX, D3S1358, D3S1611, FGA, D7S820, TH01, D13S317, D13S790, D16S539, D17S796, intron 12 BRCA1 and intron 1 TP53) that were amplified with the fluorescent AmpFlSTR Identifiler Genotyping system (Applied Biosystems, USA) and by silver nitrate staining following 6% denaturing polyacrylamide gel electrophoresis. Somatic mtDNA mutations in the D-loop site were assessed with direct sequencing of the hypervariable HVI and HVII mitochondrial regions. RESULTS: Half of the cancer tissues presented some nuclear instability. Interestingly, the D13S790 locus was the most frequently affected (36%), while the D2S123 locus presented no alterations. Forty-two percent of the cases showed somatic mitochondrial mutations, the majority at region 303-315 poly-C. We identified associations between Elston grade III, instabilities at 13q31 region (p = 0.0264) and mtDNA mutations (p = 0.0041). Furthermore, instabilities at 13q31 region were also associated with TP53 mutations in the invasive ductal carcinoma cases (p= 0.0207). CONCLUSION: Instabilities at 13q31 region and the presence of somatic mtDNA mutations in a D-loop site correlated with tumor aggressiveness.